The Relationship between Social Comparison and Body Dissatisfaction and Its Implications for the Formation of Character Values in Early Adult Students at Bina Mandiri University Gorontalo - Sitti Sulistia L. Husain; Fendi Ntobuo; Sitti Rojiyah Puhi (Jambura Journal Civic Education, 2026)
This study aims to examine the relationship between social comparison and body dissatisfaction and analyze its implications on the formation of character values in early adult female students at Bina Mandiri Gorontalo University. The method used is quantitative with a correlational design. The research population amounted to 306 active female students of the Department of Pharmacy, with a sample of 75 respondents taken using stratified random sampling techniques. Data were collected through a closed questionnaire of the Likert scale that had been validated and tested for reliability (Cronbach's Alpha 0.90), then analyzed using the Spearman correlation test  through SPSS 20. The results showed that  the level of social comparison of female students was in the medium category (64.0%) and the body dissatisfaction level  was also dominant in the medium category (73.3%). The bivariate test revealed a significant positive relationship between social comparison and body dissatisfaction with a correlation coefficient value of 0.496 and a significance level of 0.001 (p 0.05). These findings indicate that the higher the tendency of female students to make physical comparisons digitally and socially, the higher the level of dissatisfaction with their bodies. The systematic implication of this phenomenon is the degradation of character values, which is characterized by the erosion of gratitude, integrity crises due to dependence on external validation, and a decrease in mental resilience and authentic self-acceptance. The recommendation of this study is the need for higher education institutions to integrate media literacy and virtue-based character education into the curriculum. Strengthening local wisdom values such as mohuyula (mutual respect) and dila lo o'opu (living modestly) is suggested as a counter-narrative to build the moral resilience of female students in facing the pressure of beauty standards in the digital era, so that they can refocus on developing their own identity and more meaningful academic achievements.